PENGARUH LEADERSHIP EFFICACY DAN OPTIMISME TERHADAP MOTIVASI UNTUK MEMIMPIN SECARA TRANSFORMASIONAL DAN DAMPAKNYA TERHADAP EFEKTIVITAS KEPEMIMPINAN (Studi pada Pelaku Usaha UMKM di Kota Pontianak dan Kabupaten Kubu Raya) - B2041132026, RINI YULIASTI (Equator Journal of Management and Entrepreneurship (EJME), 2019)
Every businessmen has a desire to be able to develop and maintain the company he leads, including the businessmen of micro, small, and medium-scale business. Many micro, small, and medium-scale business that grow in West Kalimantan, including all of them in Pontianak and Kubu Raya regency, but for micro, small, and medium-scale business which are unable to compete or experience obstacles in general have to close their business. The data analysis technique that will be used in this research is path analysis. The results show that partially, leadership efficacy has an effect on motivation to lead in transformatively and leadership effectiveness, optimism has no effect on leadership effectiveness, but optimism influences motivation to lead transformatively, motivation has impact to lead transformatively which influence the leadership effectiveness.             Keywords :leadership efficacy, optimism, motivation to lead transformatively and leadership effectiveness